Wafting spheres: much ado about nothing. Issue 4 (11th January 2021) - Fuchs, Peter
Abstract : Purpose: The purpose of this paper is to implement the idea of the sphere on systems theory (type: Niklas Luhmann) and to test whether this theory can be used to gain a sharper approach to the complex of ideas of the sphere. The main theme is "the conceptual blurriness of the word sphere." This essay analyzes the societal and historical semantics of the concept of sphere and nearby notions in the thought traditions in medieval society until the modern, i.e. the functionally differentiated society. Nearby notions as limitationality and boundary are discussed, as well as sphere as a "lexicalized metaphor." At the end, the paper turns to the concept of sphere in modern society that is based on the distinction "public/private" and applies the discussion to the system of mass media. Design/methodology/approach: This paper can be classified as a "conceptual essay" that draws on basic systems theoretical concepts. Findings: The result of the theoretical considerations is that the word "sphere" represents nothing more than a "catchword" and can hardly lay the groundwork for empirical and theoretical research that would be instructive with regard to the new media and their massive influence on society. Originality/value: This paper was researched and written solely by the author. All sources are clearly identified.